To Compare Frequency of Complications of 18 Gauge Needle with 16 Gauge Needle in patients undergoing Renal Biopsy - Muhammad Ahmad, Sana Naseer, Muhammad Shahbaz, Muhammad Imran, Ijaz Nabi, Nouman Hameed Sheikh (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare frequency of complications of 18 gauge needle with 16 gauge needle in patients undergoing renal biopsy. Duration of study: 6 months i.e.01-07-18 to 31-12-18 Method: Randomly allocated by a computer generated random number. Sample size was 560 patients. Two equal groups A and B. 16 gauge needles were used in A and 18 gauge needles were used in B each with 280 cases. Ultrasound guided biopsies were done. An automatic biopsy gun was used. The patients were instructed to lie on bed on their back for 4-6 hours post procedure. All the information was collected on a specially designed Performa. Result: Complications of patients undergoing renal biopsy shows perinephric hematoma in 6(2.14%) cases in A and 9(3.21%) cases in B with p value 0.43, macroscopic hematuria in A is 5(1.79%) cases and 3(1.07%) cases in B with p value 0.47. Retroperitoneal hemorrhage was recorded in 3(1.07%) cases in A and no case in B and p value was 0.08. Conclusion: Both 16 gauge needle and 18 gauge needles are equally effective in renal biopsy in terms of less complication (peri nephric hematoma, macroscopic hematuria and retroperitoneal hemorrhage). Keywords: Renal biopsy, 16 gauge needle, 18 gauge needle, perinephric hematoma, retroperitoneal hemorrhage